1981
DOI: 10.1111/j.1939-0025.1981.tb01351.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of a child's age at the time of parental divorce.

Abstract: The literature on children of divorce presents three theories on the relationship between a child's age at divorce and subsequent adaptation. Outpatient evaluations of 144 children of divorce, ranging in age from seven to 17 years, were coded for nature of emotional-behavioral problems and overall degree of psychological adjustment. Divorce timing was unrelated to overall level of adjustment, but was associated significantly with different constellations of emotional-behavioral difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
3

Year Published

1984
1984
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 21 publications
4
47
0
3
Order By: Relevance
“…Kalter and Rembar (1981) found that while the impact of divorce on boys and girls may differ qualitatively, it does not differ quantitatively, that is, boys and girls suffer a similar quantity of adverse effects on their adjustment. Allison and Furstenberg (1989), looking at the effects of divorce on various measures of well-being in children and young adolescents, found no differences according to gender in the extent of negative effects suffered because of parental divorce.…”
Section: The Impact Of Gender On Adjustmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Kalter and Rembar (1981) found that while the impact of divorce on boys and girls may differ qualitatively, it does not differ quantitatively, that is, boys and girls suffer a similar quantity of adverse effects on their adjustment. Allison and Furstenberg (1989), looking at the effects of divorce on various measures of well-being in children and young adolescents, found no differences according to gender in the extent of negative effects suffered because of parental divorce.…”
Section: The Impact Of Gender On Adjustmentmentioning
confidence: 96%
“…Much of the available literature on children of divorce looks at younger children of divorce, to the point of neglecting adolescents (Amato & Keith, 1991a;Kalter, 1990;Kalter & Rembar, 1981). This suggests that this younger age group is considered to be more seriously affected.…”
Section: The Age Of the Child At The Time Of Divorcementioning
confidence: 99%
See 1 more Smart Citation
“…Deux hypothèses se présentent: la première (Hetherington, 1966(Hetherington, , 1972Gardner, 1977) soutient que plus l'enfant est jeune, plus il souffrira à court et à long terme du divorce. D'autre part, la deuxième hypothèse (Kalter et Rembar, 1981 ;McDermott, 1970 ;Neubauer, 1960 ;Westman, 1972) fait état d'un stage critique du développement, le plus souvent la période oedipienne (3 à 6 ans), où l'enfant serait plus vulnérable psychologiquement.…”
Section: Age Lors Du Divorceunclassified
“…For example, Touliatos and Lindholm (1980) found that youngsters living with fathers only and with mothers and stepfathers exhibited more conduct problems and socialized delinquency than did their peers in intact families. Several researchers (Kalter & Rembar, 1981;Schoettle & Cantwell, 1980;Touliatos & Lindholm, 1980) have reported that children from "disrupted" homes manifest behavioral problems, such as conduct, bizarre behavior, and coopera tive stealing. Jenkins argues, however, that coping with singleparenthood and the inherent problems created are compounded by the shift in the family's economic status which may occur.…”
mentioning
confidence: 99%